Biotreatment of Oil Wells Drilling Waste in an Agricultural Soil - H. Al-Joubori, Muna; A. A. H. Abd Al-Razaq, Ayad (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
One of the most important environmental issues is the responsible effective and economic treatment of drilling waste especially oily waste. In this research two fungal isolates named Pleurotus ostreatus and Trichoderma harzianum were chosen for the first time to treat biologically the oily drilled cuttings contaminated with diesel which resulted from drilling oil wells use oil based muds (OBMs). The results showed that the fungi under study utilized the hydrocarbon of contaminated soil as a source of nutrient and growth and that both fungi can be considered hydrocarbon degrading microorganisms. The used biotreatment is cost effective process since most of the materials used in the cultivation and growth of the present fungi were available and cheap agricultural waste. The best hydrocarbon degradation was observed in case of using both fungi together with 8 % by weight microorganisms concentration ratio and with the same ratio of nutrients components expressed as carbon/nitrogen/phosphorus equal to 100/60/10 with 10/1 carbon/potassium which gave average total petroleum hydrocarbon degradation of about 395 ppm per day. Good results were obtained using the new nutrients components ratio(C/N/P=100/60/10 with C/K=10) compared to other studies applied different nutrients ratios for the same type of diesel contamination.